Răspuns :
4) x²-(y-z)²=(x-y+z)(x+y-z)⇒(x-y+z)(x+y-z)=42
2x+2y-2z=12⇒2(x+y-z)=12⇒x+y-z=6
inlocuim mai sus si obtinem
(x-y+z)*6=42⇒x-y+z=7
2x+2y-2z=12⇒2(x+y-z)=12⇒x+y-z=6
inlocuim mai sus si obtinem
(x-y+z)*6=42⇒x-y+z=7
se aplica formula de calcul prescurtat a²-b²=(a-b)(a+b)
(x-y+z)(x+y-z)=42
x-y+z=42:(x+y-z) pe x+y-z il calculam din cealalta relatie
2x+2y-2z=12
2(x+y-z)=12
x+y-z=6
x-y+z=42:6=7
(x-y+z)(x+y-z)=42
x-y+z=42:(x+y-z) pe x+y-z il calculam din cealalta relatie
2x+2y-2z=12
2(x+y-z)=12
x+y-z=6
x-y+z=42:6=7